A biomarker record of temperature and phytoplankton community structure in the Okinawa Trough since the last glacial maximum. Issue 1 (20th June 2017) - Ruan, Jiaping; Xu, Yunping; Ding, Su; Wang, Yinghui; Zhang, Xinyu
Abstract: A variety of biomarkers were examined from Ocean Drilling Program Core 1202B to reconstruct temperature and phytoplankton community structures in the southern Okinawa Trough since 20 ka. Two molecular temperature proxies ( $${\rm U}_{{37}}^{{{\rm K}′}} $$ and TEX86 ) show 5°C to ~6°C warming during the glacial-interglacial transition. Prior to the Holocene, the $${\rm U}_{{37}}^{{{\rm K}′}} $$ -derived temperature was generally 1° C to 4° C higher than TEX86 -derived temperature. This difference, however, was reduced to <1° C in the Holocene. Correspondingly, the phytoplankton biomarkers (e.g., C37:2 alkenone, brassicasterol, C30 1, 15 diol, and dinosterol) indicate a shift of planktonic community structures, with coccolithophorids becoming more abundant in the Holocene at the expense of diatoms/dinoflagellates. This shift is related to the variability of nutrients, temperature, and salinity in the Okinawa Trough, likely controlled by the sea level and the intensity of the Kuroshio Current. The phytoplankton community change may have had profound implications for atmospheric CO2 fluctuations during glacial-interglacial cycles since diatoms and dinoflagellates have a higher efficiency of the biological pump than coccolithophorids.